LANGUAGE AND CULTURE. LINGUISTIC ASPECT OF INTERCULTURAL COMMUNICATION - Kushakova Nodira; Kutbiddinova Shoira; Che Zalina Binti Zulkifli (Journals Park Publishing, 2025)
This article reveals the complex and nuanced relationship between language, culture, and communication, exploring how linguistic structures reflect cultural worldviews. A significant challenge in translation arises when concepts or objects unique to one culture lack direct equivalents in another language. This linguistic gap occurs because certain words are deeply embedded in the cultural context of a language, making them untranslatable or requiring borrowing from other languages to convey their meaning. Furthermore, the same concept may be expressed differently in various languages, either excessively or insufficiently, complicating the translation process. As a result, understanding language goes beyond memorizing vocabulary—it requires grasping the natural and stable combinations of words and phrases specific to each language.
Keywords: Cultural meanings, language and communication, translation challenges, linguistic gaps, cultural context, borrowings, linguistic worldview phraseological compatibility, connotations, cognitive frameworks, language and culture.